Joint accumulations of FDG in whole body PET scans - von Schulthess, G. K.; Meier, N.; Stumpe, K. D. M. (Nuklearmedizin - NuclearMedicine, 2001)
Purpose: To retrospectively evaluate FDG accumulations in major joints in a large series of non-absorption corrected partial body and whole body FDG-PET scans, and to determine the frequency and intensity of accumulation. Materials and methods: 354 consecutive PET partialand whole body non-transmission corrected scans of patients obtained for tumor staging were examined with respect to FDG accumulations in the acromio-clavicular (AC)-, gleno-humeral-, hip-, knee- and talo-tlblal joints. FDG-uptake was graded using a semi-quantitative scale from 0 (no accumulation) to 4 (very strong accumulation comparable to brain uptake). Results: Joint activity of grade 1-2 was noted frequently, while grade 3 was rare, occurring only in the knee and shoulder joints, and grade 4 was inexistent. The 43 patients with grade 3 accumulations or with at least 4 joints showing grade 2 uptake were interviewed, but all denied pain specifically referred to a joint. Joint accumulations were seen in 50% of the acromio-clavicular-, 80% in the gleno-humeral-, 50% in the hip-, 90% in the knee and 80% in the talo-tibial joints. The intensities of joint accumulations correlated positively and significantly with patient age, ranging from r = 0.7 and ñ <0.05 in the knee to r = 0.96 and ñ <0.0001 in the AC joint. Conclusions: FDG accumulations in the joints in whole body FDG-PET scans are frequent and are very likely not related to symptoms. As there is a strong age correlation, and FDG is known to accumulate in inflammatory lesions, the findings are most likely a result of sub-clinical inflammatory synovial proliferation or other chronic inflammatory processes occurring in aging joints.
Keywords: Whole body FDG-PET; joints; osteoarthritis; inflammation; age